Analysis of Life Style Representation in the â€œInterchangeâ€ English Language Teaching Books - Hosseinifar, Aida (Mediterranean Journal of Social Sciences, 2012)
This paper tries to analyze how ideology presented in the Interchange English language teaching books is reflected. And I waslooking for the answer of this question that "How do Interchange English language teaching books, as symbolic images, transfer theirideological meaning? And how are an ideology and particular life style presented in a natural and public form in these books?" Foranswering these questions, first I studied the four yellow, red, blue and green Interchange books and found the determinants of reflectedlife styles in these books, then came up with a pattern of the particular life style reflected in the books. These patterns are considered themain strategies of the book for transferring particular views and beliefs.